2022
DOI: 10.36987/ecobi.v9i1.2032
|View full text |Cite
|
Sign up to set email alerts
|

Role of Organization Citizenship Behavior Mediation in Work Motivation Relationship to Employee Performance: Empirical Study

Abstract: This study aims to explore the effect of work motivation on organization citizenship behavior (OCB) and employee performance and the mediating role of organization citizenship behavior (OCB) on the relationship of work motivation and employee performance. The research method used is quantitative with a total sample of 83 respondents. The findings of this study reveal that work motivation has a positive and significant effect on organization citizenship behavior, organization citizenship behavior has a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
(3 reference statements)
1
5
0
2
Order By: Relevance
“…This conclusion can be reached by referring to the table that has been presented above. Therefore, values that are lower than 0.5 may be eliminated from the research construct, or one may alternatively assert that the item is invalid for the purpose of assembling latent constructs (Herdyanti et al, 2020;Muzakki & Hutabarat, 2022;Muzakki & Pratiwi, 2019;Pratiwi & Muzakki, 2021). After that, reprocessing the survey data is the next step to take if the invalid item has been deleted in the previous phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion can be reached by referring to the table that has been presented above. Therefore, values that are lower than 0.5 may be eliminated from the research construct, or one may alternatively assert that the item is invalid for the purpose of assembling latent constructs (Herdyanti et al, 2020;Muzakki & Hutabarat, 2022;Muzakki & Pratiwi, 2019;Pratiwi & Muzakki, 2021). After that, reprocessing the survey data is the next step to take if the invalid item has been deleted in the previous phase.…”
Section: Methodsmentioning
confidence: 99%
“…This meant that all of the items could be used to measure research variables (Muzakki & Hutabarat, 2022;Pratiwi & Muzakki, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted by a previous study (8), it was found that Intellectual Capital Affects performance through Work Motivation Positively and Significantly. Another study (9) found that altruism influences employee performance through work motivation in a positive and significant way. H1: Altruism, Intellectual capital behavior, and Work Motivation simultaneously affect the Medical Staff Performance.…”
Section: Literature Review the Influence Of Altruism And Intellectual...mentioning
confidence: 96%
“…Pada sebuah kajian empiris disebutkan bahwa tingginya tingkat work-family conflict secara negatif dan signifikan berpengaruh pada job satisfaction karyawan (Asbari et al, 2020;Dodanwala & Shrestha, 2021) yang tidak valid dengan perolehan nilai factor loading sebesar 0.398 di bawah nilai rujukan 0,5. Dengan demikian, nilai di bawah 0,5 dapat dihilangkan dari konstruk penelitian atau juga dapat dikatakan bahwa item tersebut tidak valid dalam menyusun konstruk laten (Herdyanti et al, 2020;Muzakki & Hutabarat, 2022;Muzakki & Pratiwi, 2019;Muzakki et al, 2021). Kemudian, apabila item yang tidak valid tersebut telah dihilangkan, langkah berikutnya yaitu melakukan pengolahan kembali terhadap data hasil survey.…”
Section: Percieved Organizational Support Workfamily Conflict Dan Job...unclassified
“…Kemudian, apabila item yang tidak valid tersebut telah dihilangkan, langkah berikutnya yaitu melakukan pengolahan kembali terhadap data hasil survey. Setelah dilakukan pengolahan kembali ditemukan bahwa semua item yang digunakan untuk mengukur variabel laten telah memenuhi kriteria yang dibutuhkan dan dapat dikatakan valid secara statistik, serta bisa digunakan untuk mengukur dalam variabel penelitian (Muzakki & Hutabarat, 2022;Muzakki et al, 2021).…”
Section: Percieved Organizational Support Workfamily Conflict Dan Job...unclassified